Perancangan Sistem Informasi Pelayanan Kantor Desa Berbasis Website Menggunakan PHP di Desa Serasah Kecamatan Pemayung Kabupaten Batang Hari - Saidul Mubarok Afifuddin Syah; Bastomi Baharsyah; Albet Triadi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
In the current era of digitalization, villages are expected to follow technological developments to modernize correspondence services. Village administration services delivered via the internet enable the village government to communicate information quickly and simply to all village officials, the community, village organizations and the community within the village. Apart from that, the community can submit input to the village government through village information services to direct development in a more positive direction. The problem in Serasah Village that often occurs is that the village head and office staff concerned with carrying out services are often not at the village office because they are out of town on business or there are sub-district meetings and currently there are additional activities in the form of training. electrical installation from BLKP Jambi. So many residents experience obstacles because of this, in fact, some residents who live far from the office area often receive less than optimal service. Based on this problem, it is necessary to design an information system at the Serasah Village office which will take the form of a website which has features regarding information regarding news and activity agendas that will be carried out at the Serasah Village Office, features for online letter submission services and checking the status of letter submissions made. by society. The system development method used to develop websites is the waterfall model. After creating the website, the website testing stage was carried out using the black box testing method with successful test results and a feasibility test was carried out using a Likert scale model. The results of the feasibility test were carried out using a questionnaire and data was obtained with an average percentage of 81.6%.